Comparison Between Two Methods of Ovulation Induction: Clomiphene Alone and Clomiphene +Tamoxifen in PCOS Patients - Mohammed , Ali Hassan (Diyala Journal of Medicine, 2019)
Background: Infertility affects about 10-15% of reproductive-age couples. About half the causes of infertility are female related and approximately 40% of the cases are caused by anovulation, mostly in PCO women. Objective: This study was conducted to determine and compare the effects of two drug treatment regimens: higher dose of clomiphene and a combination of lower dose of clomiphene and tamoxifen in treating infertile women with PCO. Materials and Methods: The study was a randomized clinical trial conducted on 100 infertile patients who referred to Albatool Infertility Clinic between the years (Jan. 2009-Dec.2009). The patients were selected who had received at least 3 periods of clomiphene, but no pregnancy had occurred. They were randomly divided into two groups. In the first group, clomiphene was increased to 100 mg and the second group 20 mg of tamoxifen was added to 50 mg of clomiphene from day 5-9 of menstruation cycle. Infertility duration, duration of medicine used, endometrial thickness, ovulation, and pregnancy rate were studied in both groups. Results: Ovulation rate in clomiphene group was 54.9%; Tamoxifen + clomiphene group was 73.5% without significant differences in both groups. (PV = 0.053). Positive pregnancy rate in clomiphene group was 39.2%; clomiphene + tamoxifen group was 61.2% (P value < 0.05). Conclusion: pregnancy rate was higher in clomiphene/tamoxifen group than in the clomiphene group. The presence of a dominant follicle in the two treatment groups in women between 18-24 was not significant, but in women between 25-39 years was significant (PV= 0.049). The recommendation is to add Tamoxifen to Clomiphene in 35-39 women with 20≤ BMI ≤26.99 before the use of gonadotropins treatment in PCOS with or without IUI(intra uterine insemination), because these options have higher risk of multiple pregnancy and ovarian hyperstimulation syndrome.